2017
DOI: 10.1021/acs.biochem.7b00156
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Structural Adaptation Differences between the Mesophilic and Psychrophilic Lactate Dehydrogenases

Abstract: The thermodynamics of substrate binding and enzymatic activity of a glycolytic enzyme, lactate dehydrogenase (LDH), from both porcine heart, phLDH (Sus scrofa; a mesophile), and mackerel icefish, cgLDH (Chamapsocephalus gunnari; a psychrophile), were investigated. Using a novel and quite sensitive fluorescence assay that can distinguish protein conformational changes close to and distal from the substrate binding pocket, a reversible global protein structural transition preceding the high-temperature transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 55 publications
(155 reference statements)
2
22
0
Order By: Relevance
“…10 Furthermore, pig heart LDH demonstrates a structural change and similar break in enzyme activity around 35°C, indicating that elevated glass transitions may not be restricted to thermophilic enzymes. 18…”
mentioning
confidence: 99%
“…10 Furthermore, pig heart LDH demonstrates a structural change and similar break in enzyme activity around 35°C, indicating that elevated glass transitions may not be restricted to thermophilic enzymes. 18…”
mentioning
confidence: 99%
“…rPsLeuDH also exhibited lower Δ H , Δ S and Δ G and higher k cat at low temperature, as compared to mesophilic enzyme, which may be mainly related to the conformation of cold adapted protein [ 27 ]. On the other hand, it may also be related to increasing the efficiency of binding of the substrate to the catalytic site [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rapid kinetics experiments and molecular dynamics simulations demonstrated that the LDH complex with NADH exists in quite a range of protein conformations with different degree of openness and solvation of the active site, whereby only a minority population of the enzyme is binding competent [50,51]. Once the enzyme-substrate complex is formed, its further catalytic conversion also proceeds through several different trajectories-the active site conformation of LDH is shown to exhibit important heterogeneity, so that the LDH reaction landscape branches at multiple points creating pathways with varied reactivity [51,73,75,76]. Importantly, the conformational transitions that control the rate of substrate binding and determine the partitioning between different catalytic branches are all associated with substantial changes in protein solvation and, consequently, large volume changes.…”
Section: A Newly Discovered Mode Of High-pressure Adaptation In Proteinsmentioning
confidence: 99%
“…Importantly, the conformational transitions that control the rate of substrate binding and determine the partitioning between different catalytic branches are all associated with substantial changes in protein solvation and, consequently, large volume changes. It makes the catalytic landscape of LDH particularly susceptible to hydrostatic pressure [77] and addition of osmolytes, such as TMAO [52,75].…”
Section: A Newly Discovered Mode Of High-pressure Adaptation In Proteinsmentioning
confidence: 99%
See 1 more Smart Citation